Combination anti–PD-1 and antiretroviral therapy provides therapeutic benefit against SIV - Mylvaganam, Geetha H. (JCI Insight, 2018)
Therapeutic strategies that augment antiviral immunity and reduce the viral reservoir are critical to achieving durable remission of HIV. The coinhibitory receptor programmed death-1 (PD-1) regulates CD8(+) T cell dysfunction during chronic HIV and SIV infections. We previously demonstrated that in vivo blockade of PD-1 during chronic SIV infection improves the function of antiviral CD8(+) T cells and B cells. Here, we tested the immunological and virological effects of PD-1 blockade combined with antiretroviral therapy (ART) in rhesus macaques. Administration of anti–PD-1 antibody 10 days prior to ART initiation rapidly enhanced antiviral CD8(+) T cell function and diminished IFN-stimulated genes. This resulted in faster viral suppression in plasma and better Th17 cell reconstitution in the rectal mucosa following ART initiation. PD-1 blockade during ART resulted in lower levels of cell-associated replication-competent virus. Following ART interruption, PD-1 antibody–treated animals showed markedly higher expansion of proliferating CXCR5(+)perforin(+)granzyme B(+) effector CD8(+) T cells and lower regulatory T cells that resulted in better control of viremia. Our results show that PD-1 blockade can be administered safely with ART to augment antiviral CD8(+) T cell function and reduce the viral reservoir, leading to improved control of viral rebound after ART interruption.